Staphylococcus aureus Bacteremia (SAB) Management in a Large Metropolitan Integrated Health Region: Quality of Care Determinants (QoCD). (4th October 2017) - Lam, John; Robinson, Stephen; Gregson, Daniel; Somayaji, Ranjani; Welikovitch, Lisa; Conly, John; Parkins, Michael
Abstract: Background: SAB is associated with significant morbidity and mortality. We undertook a study to determine how key quality determinants associated with SAB management were completed and to identify factors associated with failure to comply. Methods: Adults receiving care within an integrated health region of 1.3 million individuals with SAB from 2012–2014 were included in a retrospective analysis. Detailed chart reviews were performed to capture demographics, microbiology, investigations, treatment, and outcomes. Factors subject to QoCD included: repeat blood cultures, a transthoracic echocardiogram (TTE), infectious disease consultation (IDC), and if empiric MRSA coverage was provided. Multivariate logistic regression (STATA 14.2 (College Stn., TX)) was used to assess for statistically significant factors associated with each quality improvement metric. Results: Between 2012 and 2014, 858 individuals experienced 964 distinct episodes of SAB (19.1% MRSA). The study cohort included patients who survived ≥48 hours (97.6%). Follow-up blood cultures were completed in 832 SAB episodes, of which 68.2% were performed within 48 hours. Factors associated with failure to perform repeat blood cultures included; increasing age (OR 1.01/yr.) and lack of IDC (OR 27.97). Almost 70% of patients underwent at least a TTE (median time from SAB of 2.6 days, IQR 1.14–4.49). Factors associated with failure to perform a TTE included; increasing age (OR 1.01/yr.), co-morbid liver disease (OR 1.92), absence of systemic emboli (OR 2.00), and lack of an IDC (OR 5.36). Empiric MRSA coverage within 48 hours of blood culture occurred in 74.4%. Factors associated with lack of receipt of empiric MRSA coverage included; increasing age (OR 1.03/yr.), declining GFR (OR 1.00) or absence of toxic changes (OR 1.97) on blood work within 24 hours of SAB, lack of IDC (OR 2.07) or identified emboli (OR 2.38). Despite improved compliance with SAB quality improvement metrics only 63.4% of patients were seen by the IDC service; median time from SAB 2.72 days (IQR 1.11–5.76). Conclusion: We identified significant gaps between the treatments and investigations patients received vs. optimal management. IDC was associated with improved attainment of targeted SAB QoCD but was underutilized. Disclosures: All authors: No reported disclosures.